2013
DOI: 10.1007/s13311-013-0198-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Activation Contributes to Increased Neuronal Activity in the Posterior Thalamic Nucleus and Associated Chronic Hyperesthesia after Rat Spinal Cord Contusion

Abstract: Spinal cord injury (SCI) causes not only sensorimotor and cognitive deficits, but frequently also severe chronic pain that is difficult to treat (SCI pain). We previously showed that hyperesthesia, as well as spontaneous pain induced by electrolytic lesions in the rat spinothalamic tract, is associated with increased spontaneous and sensory-evoked activity in the posterior thalamic nucleus (PO). We have also demonstrated that rodent impact SCI increases cell cycle activation (CCA) in the injury region and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 83 publications
(136 reference statements)
6
65
1
Order By: Relevance
“…However, supratentorial changes have been reported in localized brain regions associated with pain modulation after SCI-induced hyperesthesia, including chronic inflammatory changes associated with plasticity or electrophysiological alterations (Hains et al, 2005;Hubscher and Johnson, 2006;Zhao et al, 2007;KnerlichLukoschus et al, 2011;Yoon et al, 2013). In our own recent studies examining mechanisms of SCI-induced hyperpathia in rodent models, we observed sustained neuroinflammation not only in brain regions regulating pain sensation (Wu et al, 2013b), but also more diffusely in cortex, thalamus, and hippocampus. Because the degree and pattern of changes was similar to those associated with the chronic neurodegeneration observed after traumatic brain injury (TBI) in rodents (Kumar and Loane, 2012), we initiated an independent study to determine whether brain neurodegeneration and functional neurological correlates occur after isolated thoracic SCI.…”
Section: Introductionmentioning
confidence: 59%
“…However, supratentorial changes have been reported in localized brain regions associated with pain modulation after SCI-induced hyperesthesia, including chronic inflammatory changes associated with plasticity or electrophysiological alterations (Hains et al, 2005;Hubscher and Johnson, 2006;Zhao et al, 2007;KnerlichLukoschus et al, 2011;Yoon et al, 2013). In our own recent studies examining mechanisms of SCI-induced hyperpathia in rodent models, we observed sustained neuroinflammation not only in brain regions regulating pain sensation (Wu et al, 2013b), but also more diffusely in cortex, thalamus, and hippocampus. Because the degree and pattern of changes was similar to those associated with the chronic neurodegeneration observed after traumatic brain injury (TBI) in rodents (Kumar and Loane, 2012), we initiated an independent study to determine whether brain neurodegeneration and functional neurological correlates occur after isolated thoracic SCI.…”
Section: Introductionmentioning
confidence: 59%
“…49,53 More recently, CCL21 signaling was found increased in neuronal cell bodies and parenchyma within both the hippocampus and cortex at 7 days after SCI. 19 Here, we examined CCL21 immunoreactivity in key brain regions from sham, mild, moderate, and severe SCI mice at 16 weeks post-injury.…”
Section: Ccl21 Accumulation In the Brain Following Scimentioning
confidence: 99%
“…For each experiment, data from all images from one region in each mouse were summed up and used for final statistical analysis. 49,50 Unbiased stereological quantification of microglial phenotypes and neuronal survival Brain coronal sections were stained with cresyl-violet and Stereo Investigator software (MBF Biosciences, VT) was used to count the total number of surviving neurons in the cortex, thalamus, as well as Cornu Ammonis (CA) 1, CA2/3, and DG sub-regions of the hippocampus using the optical fractionator method of unbiased stereology as described previously. 18 Every fourth 60-lm section was analyzed beginning from a random start point.…”
Section: Immunohistochemistry Image Acquisition and Quantificationmentioning
confidence: 99%
See 2 more Smart Citations